APLIKASI PERSEDIAAN BARANG MENGGUNAKAN METODE FIFO PADA CV BANDUNG JAYA - Elda Rotio Harahap; Jamaluddin Jamaluddin; Gortap Lumbantoruan (Universitas Methodist Indonesia, 2019)
Technological progress greatly affects several activities, especially in the field of work, where all work processes have used technology that further speeds up work and saves time. But in managing inventory in CV Bandung Jaya warehouse, the process of entering and leaving the goods is still recorded in the stock book, so many warehouse records and workmanship must be long and irregular, besides there is no coding for old and new items in the warehouse resulting in the warehouse clerk not knowing the items that were first sold were useful for maintaining the quality of the goods. therefore the writer takes the FIFO method (first in first out) on the research on the supply of goods at CV Bandung Jaya, because the FIFO method (first in first out) is the item that first enters, the item will first be sold, the system will make coding specifically on goods in warehouse. In addition, the system will produce more effective and accurate goods management reports.